Intra-Amniotic Infection and Sterile Intra-Amniotic Inflammation in Cervical Insufficiency with Prolapsed Fetal Membranes: Clinical Implications - Chalupska, Martina; Kacerovsky, Marian; Stranik, Jaroslav; Gregor, Miroslav; Maly, Jan; Jacobsson, Bo; Musilova, Ivana (Fetal diagnosis and therapy, 2021)
INTRODUCTION: The aim of this study was to identify the rates of 2 phenotypes of intra-amniotic inflammation: intra-amniotic infection (with microbial invasion of the amniotic cavity [MIAC]) and sterile intra-amniotic inflammation (without MIAC), and their outcomes, among women with cervical insufficiency with prolapsed fetal membranes. METHODS OF STUDY: This is a retrospective study of women admitted to the Department of Obstetrics and Gynecology, University Hospital Hradec Kralove between January 2014 and May 2020. Transabdominal amniocentesis to evaluate intra-amniotic inflammation (amniotic fluid interleukin-6) and MIAC (culturing and molecular biology methods) was performed as part of standard clinical management. RESULTS: In total, 37 women with cervical insufficiency and prolapsed fetal membranes were included; 11% (4/37) and 43% (16/37) of them had intra-amniotic infection and sterile intra-amniotic inflammation, respectively. In women with intra-amniotic infection and sterile intra-amniotic inflammation, we noted shorter intervals between admission and delivery (both p < 0.0001), and lower gestational age at delivery (p < 0.0001 and p = 0.004) and percentiles of birth/abortion weight (p = 0.03 and p = 0.009, respectively) than in those without intra-amniotic inflammation. CONCLUSIONS: Both phenotypes of intra-amniotic inflammation, with sterile intra-amniotic inflammation being more frequent, are associated with worse outcomes in pregnancies with cervical insufficiency with prolapsed fetal membranes.
Keywords: Second trimester abortion; Microbial invasion of the amniotic cavity; Physical exam-indicated cerclage; Mycoplasma; předčasný odtok plodové vody; plodová voda; retrospektivní studie; Inflammation; Rescue cerclage; Ureaplasma; Nonelective cerclage; infekční komplikace v těhotenství; Extraembryonic Membranes; Chorioamnionitis; Pregnancy; Emergency cerclage; těhotenství; Interleukin-6; MIAC; Preterm delivery; Second trimester loss; zánět; Fetal Membranes, Premature Rupture; extraembryonální obaly; Cerclage; Amniotic Fluid; chorioamnionitida; lidé; ženské pohlaví; Humans; Pregnancy Complications, Infectious; Amniocentesis; Sterile inflammation; Retrospective Studies; Microorganism; Female